2009
DOI: 10.1007/s12010-009-8606-z
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of Dilute Acid Hydrolyzed Corn Stover at High Solids Concentration

Abstract: The rheological properties of acid hydrolyzed corn stover at high solids concentration (20-35 wt.%) were investigated using torque rheometry. These materials are yield stress fluids whose rheological properties can be well represented by the Bingham model. Yield stresses increase with increasing solids concentration and decrease with increasing hydrolysis reaction temperature, acid concentration, and rheometer temperature. Plastic viscosities increase with increasing solids concentration and tend to decrease w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 25 publications
5
57
1
1
Order By: Relevance
“…The power law index is in the range of 3.0-7.8. According to data published by Ehrhardt et al [119], power law index decreased from 4.4 to 3.7 as pretreatment severity was increased. An opposite trend can be observed from data published by Viamajala et al [117], where pretreated samples had higher power law indices than untreated samples.…”
Section: Rheology Of Lignocellulosic Biomassmentioning
confidence: 93%
See 2 more Smart Citations
“…The power law index is in the range of 3.0-7.8. According to data published by Ehrhardt et al [119], power law index decreased from 4.4 to 3.7 as pretreatment severity was increased. An opposite trend can be observed from data published by Viamajala et al [117], where pretreated samples had higher power law indices than untreated samples.…”
Section: Rheology Of Lignocellulosic Biomassmentioning
confidence: 93%
“…Dasari and Berson [116] found that viscosity of 10% (w/w) oak sawdust slurries decreased from 3000 cP for particle size range of 150 μm < x ≤ 180 μm to 61.4 cP for particle size range of 33 μm < x ≤ 75 μm. Acidic pretreatment removes hydrophilic xylan polymer, which increases free water in the slurry and reduces particle size [117,119]. Ehrhardt et al [119] found that increasing either pretreatment temperature or acid concentration resulted in decrease in yield stress and plastic viscosity of dilute acid pretreated slurries.…”
Section: Rheology Of Lignocellulosic Biomassmentioning
confidence: 99%
See 1 more Smart Citation
“…While viscosity provides useful information, rheological characterization can further this understanding through parameters, such as yield stress and viscoelastic properties (Funk and Dinger, 1994). Yield stress, the minimum stress required to induce flow in a material, has been studied substantially for both pretreated (Pimenova and Hanley, 2003;Knutsen and Liberatore, 2009;Stickel et al, 2009;Ehrhardt et al, 2010;Lavenson et al, 2011;Senturk-Ozer et al, 2011;Wiman et al, 2011;Samaniuk et al, 2012;Zhang et al, 2014) and enzymatically hydrolyzed (Roche et al, 2009;Viamajala et al, 2009;Geddes et al, 2010;Knutsen and Liberatore, 2010) feedstocks. But this parameter can be measured only on offline samples and not always in real time.…”
Section: Introductionmentioning
confidence: 99%
“…Yield stresses for lignocellulose obtained from pretreated corn stover (PCS) in this range of insoluble solids have been reported on the range of 10-80 Pa [6], though some have reported as low as 2.42 Pa [7]. The literature describes a strong relationship between yield stress and concentration, with a 5-% change in solids concentration leading to an order of magnitude change in yield stress in some studies [6,7], while another reports change by a factor of 3 [8]. Pseudoplasticity, or shear-thinning behavior, has also been consistently observed [9].…”
Section: Introductionmentioning
confidence: 99%